A polymer–lipid membrane artificial cell nanocarrier containing enzyme–oxygen biotherapeutic inhibits the growth of B16F10 melanoma in 3D culture and in a mouse model - Yun Wang; Thomas Ming Swi Chang (Artificial Cells, Nanomedicine, and Biotechnology, 2021)
Melanoma is a deadly skin cancer. Surgery is effective for early stages but there may be remnant cells. Treatments of later stages are associated with severe side effects. Moreover, a dangerous type of melanoma cannot be detected early enough for surgery. There is an urgent need for treatment with less severe side effects. We use a novel system of artificial cell polymer–lipid membrane nanocarrier containing a biomolecular nano-system of enzyme–oxygen biotherapeutic. In this report we show (1) its effectiveness and mechanisms in inhibiting the growth of melanoma in a 3D culture collagen medium that is more similar to that in the animal. (2) This allows us to design and carry out animal studies to successfully show that this can inhibit the growth of melanoma in an animal model. This includes following the tumour sizes and body weights every 2 days for 30 days followed by histology of the sites of injection and vital organs. We also analyze the action of the different components of the nanocarrier–nano-biotherapeutic complex. In conclusion, the results show the safety and clinical feasibility of this approach in the animal model and encourages further study towards clinical use.